A comparison of the social, religious, and gender role attitudes of Catholic and Protestant women in the Republic of Ireland twenty-first century Ireland from a woman's perspective - Craven, Florence E. V. (Lewiston : Edwin Mellen Press, 2010)
This study is unique in that it analyzes the attitudes of a female sample stratified according to religious tradition (Catholic/Protestant). The sample was also stratified by age (21-45/46-70 years) and location (rural/urban). Irish sociological, social psychological and feminist scholarship has produced diverse work concerning many facets of Irish women?s lives, but little research has specifically focused on the attitudes of Irish Protestant and Catholic women as distinct groups.
Chapter 4 -- Factor Analytic Results for the Total, Catholic and Protestant SamplesChapter 5 -- Percentages and Independent Sample Means for the Social, Religious and Gender-Role Attitudes of Catholic and Protestant Women; Chapter 6 -- The Effects of Religion, Age and Location on the Social, Religious and Gender Role Attitudes of Catholic and Protestant Women; Chapter 7 -- Correlations between Factors measuring the Social, Religious and Gender Role Attitudes of Catholic and Protestant Women; Chapter 8 -- Summary and Discussion; Appendices; Bibliography; Index.
Description based on print version record.
Keywords: Women -- Ireland; Protestant women -- Ireland; Catholic women -- Ireland; Catholic women -- Ireland; Protestant women -- Ireland; Women -- Ireland; SOCIAL SCIENCE / General; Electronic books